Effects of sparger pore size, frother concentration, and air flow rate on bubble size distribution - Battung, Christine T. (2012)
This study aims to investigate the formation of gas bubbles and changes in the bubble size distribution as a function of sparger pore size, frother concentration, and air flow rate. Bubbles are generated in a cylindrical acrylic column by sparging compressed air through a single-pore needle with varying pore diameters of 0.40, 0.60, 0.80, and 1.10mm. Bubble formation is observed in the absence and presence of frother with varying concentrations of 0.20%, 0.38%, and 0.50% by volume and is analyzed under different conditions of air flow rates of 120, 360 and 600 mL/min. Nasfroth 240, one of the most common glycol-based surfactants, is used as the frother in this study. Bubble formation and generation are monitored by performing measurements of bubble diameter and changes in bubble configurations using the Image J Software. Increasing the sparger pore size results in the increase of bubble size produced, with the 1.10mm sparger pore-size consistently exhibiting the largest Sauter mean diameter. However, sparger pore size only affects the bubble size distribution in high air flow rates. Sparger pore-size affects bubble size due to the capillary pressure occurring between the area below the gas sparger and the hydrostatic forces above it which resist bubble formation. Similarly, increasing the air flow rate also increases the bubble size, with the Sauter mean diameter for the 600mL/min runs, consistently being the largest. Bubbles generated with the highest air flow rate also gives the widest bubble size distribution curves because of turbulence with the system which interferes with the absorption of frothers. The addition of frother, however, exhibits an opposite effect, wherein increasing frother concentration up to the critical coalescence concentration (CCC) condition results in the decrease in the Sauter mean diameter of the bubbles. It is also observed that in the presence of frother, more homogenous bubble sizes are produced. These effects can be attributed to the ability of frothers to prevent coalescence of bubbles, thus, preserving their initial size upon generation. Moreover, under dynamic conditions, bubble collision is more evident leading to bubble break-up and coalescence. Coalescence results in the formation of larger bubbles while the break-up mechanism leads to the formation of very minute bubbles called the daughter bubbles.